2020
DOI: 10.1111/dth.14131
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cutaneous melanoma: Demographics, prognostic factors, and survival outcomes

Abstract: Several recent studies have reported a considerably higher overall survival (OS) rate in females in various geographic regions This study further investigates the characteristics of melanoma that contribute to OS of women residing in the United States. Chi-square, Kaplan-Meier, and Cox regression models were used to analyze differences in demographics, treatment, and survival of invasive cutaneous melanoma in men and women diagnosed from 2004 to 2016 in the National cancer database. In 316 966 patients met inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 31 publications
8
45
1
1
Order By: Relevance
“…Furthermore, significant gender-specific differences were identified in Eotaxin and MCP-1 expression (Table 6), as well as in GM-CSF, TNF-α, IL-9, MIP-1a, IL-8, PDGF-BB, and MCP-1 (Tables S3-S5). This finding indicated the molecular bases possibly underlying the different incidence and different mortality rates in male vs. female melanoma [28][29][30][31][32], as well as the unexpected better response of immunotherapies in men than in women [33].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, significant gender-specific differences were identified in Eotaxin and MCP-1 expression (Table 6), as well as in GM-CSF, TNF-α, IL-9, MIP-1a, IL-8, PDGF-BB, and MCP-1 (Tables S3-S5). This finding indicated the molecular bases possibly underlying the different incidence and different mortality rates in male vs. female melanoma [28][29][30][31][32], as well as the unexpected better response of immunotherapies in men than in women [33].…”
Section: Discussionmentioning
confidence: 98%
“…Inferior clinical outcomes have been observed in men compared to women with melanoma. In a study comparing melanoma outcomes in men and women, Behbahani et al reported that men were diagnosed at 61 years of age, while women were diagnosed earlier at a median age of 55 years [28]. In the same study, women had a mean OS of 11.1 years and a 10-year survival rate of 73.1%, while men had a mean OS of 9.6 years and a 10-year survival rate of 58.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with those reported by the Cancer Research UK database which reported 5-year net survival rates of 92.4% in women and 87.6% in men in the 2010-2011 period (39). The survival advantage of women in melanoma is well-established (10,40,41). A recent large analysis from the U.S. Surveillance, Epidemiology, and End Results (SEER) cancer database showed significantly better 3-and 5-year cancer-specific melanoma survival rates among women compared to men (40), and Behbanani et al also reported better 5-year overall survival for female melanoma patients based on the U.S. National Cancer Registry (10).…”
Section: Discussionmentioning
confidence: 99%
“…The survival advantage of women in melanoma is well-established (10,40,41). A recent large analysis from the U.S. Surveillance, Epidemiology, and End Results (SEER) cancer database showed significantly better 3-and 5-year cancer-specific melanoma survival rates among women compared to men (40), and Behbanani et al also reported better 5-year overall survival for female melanoma patients based on the U.S. National Cancer Registry (10). The positive prognostic significance of female sex may be explained by various factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation